2020
DOI: 10.2147/ott.s261799
|View full text |Cite
|
Sign up to set email alerts
|

<p>MiR-140 Resensitizes Cisplatin-Resistant NSCLC Cells to Cisplatin Treatment Through the SIRT1/ROS/JNK Pathway</p>

Abstract: Background: Although cisplatin is an effective chemotherapeutic drug that is commonly used for non-small-cell lung cancer (NSCLC) treatment, the drug resistance usually occurs during the long-term use of it. It is urgent to develop strategies to reduce the resistance of NSCLC cells to cisplatin. Methods: Cisplatin-resistant NSCLC cell lines (PC9/R and A549/R) were acquired through long-term exposure of PC9 and A549 cells to cisplatin. QRT-PCR analysis was performed to compare the expression of miR-140 between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Cisplatin can perform its apoptosis-related activity in cancer cells via modifying ovarian carcinoma and increasing the formation of reactive oxygen species (ROS) [3]. Oncogenic cells have a Contrast Media & Molecular Imaging greater capacity to respond to the anticancer drug cisplatin when Smad2/3 is activated [21]. e activation of Smad2/3 results in an increase in the synthesis of apoptosis-related proteins and a reduction in the activity of antiapoptotic proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin can perform its apoptosis-related activity in cancer cells via modifying ovarian carcinoma and increasing the formation of reactive oxygen species (ROS) [3]. Oncogenic cells have a Contrast Media & Molecular Imaging greater capacity to respond to the anticancer drug cisplatin when Smad2/3 is activated [21]. e activation of Smad2/3 results in an increase in the synthesis of apoptosis-related proteins and a reduction in the activity of antiapoptotic proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In increasing CP sensitivity, miRNA-140 down-regulates SIRT1 expression to promote ROS levels. Then, ROS induces JNK phosphorylation to increase CP-mediated apoptosis [113]. As more experiments are performed, different molecular pathways are revealed that mediate CP resistance of thoracic cancers.…”
Section: Cisplatin Resistancementioning
confidence: 99%
“…They published evidence that overexpression of miR-29b re-sensitized OR-SW480 cells to oxaliplatin treatment. MiR-140 also re-sensitizes cisplatin-resistant NSCLC cells to cisplatin treatment through the SIRT1/ROS/JNK pathway ( 29 ).…”
Section: Discussionmentioning
confidence: 99%